Surface Roughness in Nanofluid Minimum Quantity Lubrication Milling of AISI 430 Ferritic Stainless Steel - Uysal, Alper (AMER SOC TESTING MATERIALS, 2017)
Stainless steels have been used in different fields such as automotive, aerospace, construction, medical instruments, etc. and machining operations have been applied in many of these sectors. However, machinability of stainless steel is difficult due to their hardening tendency and low thermal conductivity. In addition, researchers have struggled with improving the surface quality of machined stainless steel parts. For this reason, a surface roughness investigation was carried out in MQL (minimum quantity lubrication) milling of AISI 430 ferritic stainless steel. The experiments were conducted using uncoated and TiN (titanium nitride) coated WC (tungsten carbide) cutting tools under dry, pure MQL and nanofluid MQL conditions. A commercial vegetable cutting fluid was used as a base fluid and two nanofluids were prepared by adding 0.5 and 1 weight percent nanographene particles to the vegetable cutting fluid. In MQL milling operations, MQL flow rates were adjusted at 20 and 40 mL/h and spindle speed, feed rate, and depth of cut were selected as 995 rpm, 180 mm/min, and 0.5 mm, respectively. Depending on the experimental results, lower surface roughness values were obtained in nanofluid MQL milling due to the cooling and lubrication effects of nanographene particles.
Keywords: MQL milling; nanofluid; nanographene; ferritic stainless steel; surface roughness; TOOL WEAR; CUTTING PARAMETERS; VEGETABLE-OIL; MACHINABILITY; DRY; FLUIDS; ALLOY; Materials Science